Impact of Mentoring on At-Risk Youth - Shazia Mirza (Research in Social Sciences and Technology- OpenED Network, 2018)
This study is a Qualitative case study which highlights the important role of an educational leader using mentoring and socio emotional techniques to save her student from extremist activities in name of religion. Educational leaders should be committed not only toward their students' academic enrichment but also focus on developing their student's socio emotional wellbeing. The educational leader plays a profound role toward promoting students wellbeing, giving them a message that yes we are here for you and by building in them confidence when they need it the most. Whenever at-risk youth is mentioned, it is assumed that they hide destructive layers under their body and mind. They need someone who knows how to read these signs and the educational leader plays a key role in this regard. This study will help educational leaders and managers to understand the aspects, importance and applicability of social emotional learning (cognitive affective) on student's behavior. Furthermore the study also shows how using some techniques of care, the teacher not only saved her students' life but also the lives of many students. This research accentuates the importance of creating a strong bonding with students. For curriculum developers, it is of key importance to inculcate religious content that emphasizes more on aspects related to care through animal rights in Islam and humanity on whole. Furthermore this research provides imperative guidelines to inculcate social emotional learning in Islamiat curriculum and shares the result on student's behavior towards general people. It also emphasizes the leaders' role of managing students on the basis of socio emotional learning.